Direct Carboxylation of Aryl Tosylates by CO2 Catalyzed by In situ‐Generated Ni0. Issue 11 (30th October 2015) - Rebih, Fatima; Andreini, Manuel; Moncomble, Aurélien; Harrison‐Marchand, Anne; Maddaluno, Jacques; Durandetti, Muriel
Abstract: A novel Ni 0 ‐catalyzed carboxylation of aryl tosylates with carbon dioxide has been achieved under moderate temperatures and atmospheric pressure. In this procedure, the active Ni 0 species is generated in situ by simply mixing the Ni 0 precatalyst [NiBr2 (bipy)] with an excess of manganese metal. This approach requires neither a glove‐box nor the tedious preparation of sophisticated intermediate organometallic derivatives. This mild, convenient, and user‐friendly process is successfully applied to the valorization of carbon dioxide and the synthesis of versatile reactants with broad tolerance of substituents. Abstract : Direct carboxylation of aryl tosylates by CO2 is rendered possible by a Ni 0 catalyst, generated in situ by reduction of [NiBr2 (bipy)] with manganese metal. This approach, which requires neither a glove‐box nor the preparation of a sensitive organometallic derivative, is applicable to a wide range of aromatic phenols, bearing either electron‐donating or ‐withdrawing substituents.